Daunorubicin-cytarabine liposome (CPX-351) in the management of newly diagnosed secondary AML: A new twist on an old cocktail. Issue 2 (June 2019) - Maakaron, Joseph E.; Mims, Alice S.
Abstract: Initial therapy for acute myeloid leukemia (AML) remained stagnant for approximately four decades despite advances in improved understanding of pathogenesis and prognostication of the disease.      Treatment has typically consisted of an anthracycline combined with continuous infusion of cytarabine for 7 days, the "7 + 3" regimen. Attempts have been made to improve on this regimen with modest improvements in response rates but no change in overalll survival, until the recent introduction of mutation-specific agents. However, the re-vamping of the delivery of both daunorubicin and cytarabine in a liposomal encapsulation, known as CPX-351, did show improvements of overall survival compared to traditional 7 + 3 in newly diagnosed secondary and therapy-related AML in patients aged 60–75. This led to the Food and Drug Administration (FDA) approval of the agent for both of these subtypes of AML in August of 2017. Herein we will review the rationale and preclinical development of CPX-351 and discuss the pivotal studies that led to its FDA approval.